AKUNTABILITAS PELAPORAN ALOKASI DANA DESA DI DESA SANI-SANI KECAMATAN SAMATURU KABUPATEN KOLAKA - Burhan, Aulia; Kartomo, Kartomo; Surianto, Surianto (Komunitas Manajemen Kompetitif, 2025)
This study aims to determine the Accountability of Allocation Reporting Village Funds in Sani Sani Village, Samaturu District, Kolaka Regency. This study employs a qualitative research method with a descriptive approach. The research was conducted in Sani-Sani Village, Samaturu District, Kolaka Regency. Data were gathered through observations, interviews, and documentation. The data analysis process involved data collection, data presentation, verification, and conclusion drawing. The findings of this research show that the accountability of Village Fund Allocation (ADD) reporting in Sani-Sani Village, Samaturu District, Kolaka Regency generally complies with the 31 reporting indicators outlined in Ministry of Home Affairs Regulation Number 20 of 2018. However, some inconsistencies remain, particularly in the preparation and consolidation of reports. These issues are primarily due to delays in the reporting process, as the village head typically submits reports in August, resulting in late submission to the sub-district head.